Comparative effectiveness of furosemide vs torasemide in symptomatic therapy in heart failure patients: A randomized controlled study protocol. Issue 7 (19th February 2021) - Li, Yifan; Li, Li; Guo, Zhipeng; Zhang, Shunye
Abstract: Background: We performed this randomized controlled study protocol to investigate the efficacy and adverse effects of furosemide vs torasemide in patients with heart failure (HF). Method: The present study was authorized by the local research ethics committee of Shanxi Cardiovascular Hospital (no. 48736645) and informed consent was obtained from all patients. Patients were enrolled in a consecutive prospective manner on a voluntary basis. Patients who were aged 18 years and older with HF who were eligible to enroll in this randomized trial. All patients had evidence of left ventricular systolic dysfunction, confirmed by echocardiographic or nuclear imaging. The exclusion criteria were left ventricular diastolic dysfunction only, or receipt of medical or pharmaceutical care in other health systems. The primary efficacy end point was the change in procollagen type I carboxyterminal peptide (PICP) serum levels between baseline and final visit. Secondary efficacy variables included parameters related to the clinical course of HF, such as body weight, presence of edema, signs and symptoms of HF, electrocardiogram and echocardiographic evaluation, amino-terminal pro brain-type natriuretic peptide (NT-proBNP) serum levels measured by ELISA method, systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate, and renal function. Results: One hundred patients who met the inclusion criteria were included in our study, Table 1 showed the effects of furosemide and torsemide on measures of clinical outcomes. Discussion: Fluid overload is the primary cause of hospitalization among patients with HF. Preventing circulatory congestion requires careful control of dietary sodium and chronic administration of loop diuretics. Torasemide and furosemide are representatives of loop diuretics with an identical diuretic mechanism, but different pharmacokinetic properties and additional effects. There is a need for reliable conclusion regarding the comparison of furosemide and torasemide in patients with HF. Several limitation should be noted: the small number of participants did not enable assessment of the impact of torasemide and furosemide in different clinically relevant subgroups that is, elderly, patients with chronic kidney disease, dilated cardiomyopathy; short-term follow up might lead to underestimation of the complications; methodological weakness in study design may affect the results. Future high quality studies were still required.